2007
DOI: 10.1158/1078-0432.ccr-06-2318
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Trial of CTLA-4 Blockade with Human Anti-CTLA-4 in Patients with Hormone-Refractory Prostate Cancer

Abstract: Purpose: Blockade of the T-cell inhibitory receptor CTL-associated antigen-4 (CTLA-4) augments and prolongsT-cell responses and is a strategy to elicit antitumor immunity. The objectives of this pilot study were to establish the pharmacokinetic and safety profile for a single dose of 3 mg/kg of the anti-CTLA-4 antibody Ipilimumab (MDX-010, BMS-734016) and to assess if this therapy resulted in prostate-specific antigen (PSA) modulation and the development of polyclonal T-cell activation and/or clinical autoimmu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
213
0
6

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 371 publications
(223 citation statements)
references
References 17 publications
2
213
0
6
Order By: Relevance
“…This "triple immunotherapy" looks particularly promising especially as all components of the "triple immunotherapy" have approved human equivalents or are undergoing clinical trials. Clinical trials have investigated TGF-β blockade [52] and denileukin diftitox (Ontak) to deplete Treg cells in a number of different cancers [53][54][55] while the use of anti-CTLA4 Ig (Ipilimumab, Bristol Myers Squibb) was approved for the treatment of melanoma based on a recent phase III clinical trial [56]. Although many of these Treg cell depletion strategies are showing promise, it is unlikely that they will be used as a single modality to treat an advanced stage mesothelioma patient.…”
Section: Improved Survival Results From Treg Cell Depletionmentioning
confidence: 99%
“…This "triple immunotherapy" looks particularly promising especially as all components of the "triple immunotherapy" have approved human equivalents or are undergoing clinical trials. Clinical trials have investigated TGF-β blockade [52] and denileukin diftitox (Ontak) to deplete Treg cells in a number of different cancers [53][54][55] while the use of anti-CTLA4 Ig (Ipilimumab, Bristol Myers Squibb) was approved for the treatment of melanoma based on a recent phase III clinical trial [56]. Although many of these Treg cell depletion strategies are showing promise, it is unlikely that they will be used as a single modality to treat an advanced stage mesothelioma patient.…”
Section: Improved Survival Results From Treg Cell Depletionmentioning
confidence: 99%
“…A compelling precedent for abrogating inhibitory T cell signaling to enhance antitumor immunity has been established with the experience of CTLA-4 blockade (34-37). CTLA-4 blockade has also recently been investigated in patients with hormone-refractory prostate cancer (38). One distinct difference between CTLA-4 and other B7-CD28 members is that CTLA-4 ligand expression is limited to ''professional'' antigen presenting cells (dentritic cells, macrophages, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…A number of these mAb have been shown to enhance immune responses when delivered systemically. 13,14 However, human studies have shown that such systemic delivery can lead to adverse effects [15][16][17][18][19][20] Thus, an advantage of our strategy is that by co-injecting antibody-secreting and antigen-presenting DC, secretion of antibody in the vicinity of DC presenting tumor antigen to T cells may skew the resulting enhanced immune response toward tumor-specific T cells while decreasing potential non-specific autoimmune reactions. We saw the enhancement of CTL responses only when the anti-GITR-secreting DC and antigen-presenting DC were co-injected at the same site and not when they were injected in opposite sites (Figure 4b).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in mice have shown that these systemically delivered mAbs can produce the desired effect of enhancing protection against tumors and infectious diseases and many mAbs are currently in clinical trials with promising preliminary results. 13,14 However, immunomodulatory mAbs have been associated with adverse side-effects associated with their systemic administration, as observed in clinical trials with anti-CTLA-4 [15][16][17][18][19] and systemic and non-specific induction of inflammatory mediators as seen in the trial of the superagonistic mAb targeting CD28. 20 Another consideration in using these mAbs is that they are generally given in high doses (1-20 mg kg À1 ) over a period of time, resulting in expensive treatment costs.…”
Section: Introductionmentioning
confidence: 99%